2010
DOI: 10.1073/pnas.0912670107
|View full text |Cite
|
Sign up to set email alerts
|

AtBAG7 , an Arabidopsis Bcl-2–associated athanogene, resides in the endoplasmic reticulum and is involved in the unfolded protein response

Abstract: The Bcl-2-associated athanogene (BAG) family is an evolutionarily conserved, multifunctional group of cochaperones that perform diverse cellular functions ranging from proliferation to growth arrest and cell death in yeast, in mammals, and, as recently observed, in plants. The Arabidopsis genome contains seven homologs of the BAG family, including four with domain organization similar to animal BAGs. In the present study we show that an Arabidopsis BAG, AtBAG7, is a uniquely localized endoplasmic reticulum (ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
155
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 131 publications
(164 citation statements)
references
References 50 publications
5
155
2
1
Order By: Relevance
“…In particular, human and plant BAG proteins show high degrees of structural conservation in the functional portions of the protein (e.g., helical structure and hydrophobicity; Doukhanina et al, 2006) that when taken together account for functional similarity. In accordance, our studies have indicated that plant BAG family members are also multifunctional and similar to their animal counterparts, as they block several biotic and abiotic cell death-mediated processes while conferring cytoprotection in situations ranging from pathogen attack to drought stress to plant development (Doukhanina et al, 2006;Williams et al, 2010).…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…In particular, human and plant BAG proteins show high degrees of structural conservation in the functional portions of the protein (e.g., helical structure and hydrophobicity; Doukhanina et al, 2006) that when taken together account for functional similarity. In accordance, our studies have indicated that plant BAG family members are also multifunctional and similar to their animal counterparts, as they block several biotic and abiotic cell death-mediated processes while conferring cytoprotection in situations ranging from pathogen attack to drought stress to plant development (Doukhanina et al, 2006;Williams et al, 2010).…”
Section: Introductionsupporting
confidence: 77%
“…The BAG genes constitute a broadly conserved gene family and function as adapter proteins/cochaperones, forming complexes with signaling molecules and molecular chaperones including Hsp70 (Kabbage and Dickman, 2008;Williams et al, 2010). In mammals, BAG proteins are associated with several key cellular processes, including apoptosis, autophagy, proliferation, differentiation, and stress signaling (Takayama et al, 1999;Song et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations